2022
DOI: 10.1093/nar/gkac230
|View full text |Cite
|
Sign up to set email alerts
|

YY1 safeguard multidimensional epigenetic landscape associated with extended pluripotency

Abstract: Although extended pluripotent stem cells (EPSCs) have the potential to form both embryonic and extraembryonic lineages, how their transcriptional regulatory mechanism differs from that of embryonic stem cells (ESCs) remains unclear. Here, we discovered that YY1 binds to specific open chromatin regions in EPSCs. Yy1 depletion in EPSCs leads to a gene expression pattern more similar to that of ESCs than control EPSCs. Moreover, Yy1 depletion triggers a series of epigenetic crosstalk activities, including changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 95 publications
0
16
0
Order By: Relevance
“…The studies of Donohoe (Donohoe et al, 1999) and Gabriele (Gabriele et al, 2017) both indicated proved that haploinsufficiency of the YY1 gene was the main genetic basis of this syndrome. Haploinsufficiency of the YY1 gene can result in extensive loss of H3K28 acetylation, which makes the H3K27 substrate available for PrC2‐mediated methylation, thereby inhibiting gene expression (Dong et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The studies of Donohoe (Donohoe et al, 1999) and Gabriele (Gabriele et al, 2017) both indicated proved that haploinsufficiency of the YY1 gene was the main genetic basis of this syndrome. Haploinsufficiency of the YY1 gene can result in extensive loss of H3K28 acetylation, which makes the H3K27 substrate available for PrC2‐mediated methylation, thereby inhibiting gene expression (Dong et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Since DNA demethylation and reactivation of the X chromosome are the slowest reprogramming events [ 33 , 45 ], it is expected that these events may also occur relatively slowly during extended pluripotential reprogramming. Given that EPSCs have distinct epigenomic networks compared to naïve ESCs [ 11 , 46 ], observing time-course changes during cell-fusion-induced reprogramming may provide novel epigenetic and mechanistic insights into a totipotent state. For example, Mai et al identified a novel transient reprogramming regulator, NKX3-1, using a cell-fusion-mediated heterokaryon model [ 47 ], suggesting that fusion-induced reprogramming could be a promising model for identifying early reprogramming factors [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with previous reports that the formation of blastoids, or synthetic preimplantation embryos, using EPSCs resulted in a rare trophectoderm-like population compared to hypoblast- and epiblast-like contents [ 12 , 13 ]. In fact, the differentiation potential of EPSCs toward extraembryonic ectodermal lineages is highly diverse depending on the culture conditions [ 46 , 50 ], suggesting the importance of setting optimal differentiation conditions toward extraembryonic ectoderm.…”
Section: Discussionmentioning
confidence: 99%
“…In embryonic stem cells, YY1 activates transcription by targeting promoters and super-enhancers through the BAF complex [ 41 ]. YY1 is also a master regulator to coordinate multidimensional epigenetic crosstalk associated with expanded pluripotency, and depletion of YY1 disrupts specific enhancer–promoter interactions in expanded pluripotent stem cells (EPSC) [ 42 ]. Further, YY1 directly interacts with CTCF and they work together to regulate X chromosome binary switch [ 43 ].…”
Section: Protein Partners Of Ctcfmentioning
confidence: 99%